Design and Implementation of Electronic Control System of Blood Pump for Hemodialysis Machine - Andi Iswahyudi; Pratondo Busono; Yaya Suryana; Anwar Mujadin; Dwi Astharini (Universitas Al Azhar Indonesia, 2017)
Abstract – there are three methods of renal therapies, hemodialysis is the primary choise. This is because of the cheaper price compared to the CAPD. In addition, people in indonesia are still not understand the CAPD method. However, there are still many problems in the therapy using hemodialysis machine. This research aims to develop and to know the performance of the electronic control system for blood pump to match the ideal flowrate that will be used in hemodialysis treatment. This research resulting the blood pump charateristic is 179,4 step/ml when using glucose 10% and 168,2 step/ml when using glucose 20%. Based on fluid density, glucose 20% have the best performance with relative of error 0,06% at rpm 5 with 400 ml volume desired. From the result with rpm variation, the system has linearity with the slope M = 8970 step/ml = 4,2 rotation/ml using glucose 10%, and M = 8410 step/ml = 3,97 rotation/ml using glucose 20%. Which mean the slope is equivalent with the increased volume around 48,4 - 53,3 ml. It mean the blood pump rotation is constant and the system is working according the flowrate desired. It is found from the result, that many hardware factors can reducing the blood pump performance such as the roller degradation and the flexibility of the hose. Keywords – Renal Disease, Hemodialysis, CAPD, Blood pump, Flowrate